Mapeamento das necessidades formativas do formador de professores atuante no programa de formação online de mentores - Malheiro, Cícera Aparecida Lima (2017)
The reflexions of this study are embedded in a context of continuing training in-school developed under the Online Training Program of Mentors (known as PFOM). It is a set of issues related to teachers of basic education, both teachers' trainers (TT) and beginning teachers (BT). The questions are related to training needs and professional learning (and consequently professional development) of these educators. The central questions were: Considering the development of PFOM, TT mobilized what knowledge, from those indicated in the literature as appropriate to their role? These professionals have presented training needs related to activities concerning the mentorship process? Which were them? Do these needs relate to those reported by the BT followed up? The main objective was: identify the training needs of the TT of PFOM and understand the relation between the knowledge mobilized in their acting as mentors. Methodological design was carried out through qualitative approach having as research object narratives produced by TT and by BT during the participation in the PFOM. Data were analyzed using the content analysis techniques supported by the ATLAS.ti software. Results evidenced that, although the guiding principles of PFOM were the same, each trainer has developed his own interpretations about mentorship processes. Such interpretations were influenced by realities and contexts of individual performances, as well as by tasks performed by these teachers. We identified that during their performance as mentors, TT mobilized the following set of knowledge: i) being able to understand the demands of BT; ii) know to analyse the steps of the training process; iii) know to seek information and make partnerships; iv) know to organize reflections and communications on training practices; v) knowledge of experience, the ability to act in the face of educational practices; vi) know to organize training strategies; vii) know to learn from the relationship between trainer and BT; viii) know to have a good interpersonal relationship. Apparently, TT and BT have presented different training needs. Training needs voiced by TT while performing the role of mentors were configured in the context of management and establishment and organization of strategies in the face of adult education. BT training needs were linked to: indiscipline, literacy, classroom management, inclusion and curriculum of early childhood education. Mentorship contributed to disruption of difficulties faced in the continuing training in-school, allowing a more horizontal formation with the participation of both parties (trainer and subject) in the structuring of the processes. It also met the real needs of participants. Since it is very difficult for a single professional to handle working alone in the training of teachers, it was clear the importance of mobilizing partnerships within the networks and/or educational systems and within school itself. Establishment of support networks proved to be fundamental to meet the training demands presented and favour the processes of continuing training in-service.